Impact of Supervision and Workload on Internship Performance of Hospitality Students - Nizam, Syahrul; Ferdian, Feri (LITPAM, 2026)
This study examines the effects of supervision and workload on the internship performance of hospitality students. The study is grounded in the need to strengthen vocational higher education internship programs, particularly in hospitality settings where students are placed in hotels with different operational standards and are expected to perform simultaneously as learners and temporary workplace participants. Internship performance was measured through accuracy, work results, speed, and target achievement; supervision through monitoring, observation, and feedback; and workload through task quantity, work time, and physical and mental demands. The study employed a quantitative causal-associative design involving 97 internship students from the 2022 cohort of the D-IV Hospitality Management Study Program at Padang State University. Data were collected using a five-point Likert questionnaire consisting of 30 items. Instrument testing confirmed validity for all items, with corrected item-total correlations ranging from 0.650 to 0.915 for supervision, 0.716 to 0.878 for workload, and 0.601 to 0.911 for internship performance. Reliability was also strong, with Cronbach's Alpha values of 0.945, 0.918, and 0.956, respectively. The results show that supervision and workload simultaneously have a significant effect on internship performance (F = 15.355; p < 0.001). Partially, supervision has a positive and significant effect (B = 0.441; p = 0.004), and workload also has a positive and significant effect (B = 0.312; p = 0.042). The coefficient of determination (R Square = 0.246) indicates that supervision and workload explain 24.6% of the variation in internship performance. These findings imply that universities and hospitality industry partners should strengthen structured supervision and ensure that internship workloads remain proportional to students' learning capacity.